2022
DOI: 10.3390/ijerph191710953
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Interventions That Promote Sleep in Preterm Newborns in the Neonatal Intensive Care Units: An Integrative Review

Abstract: Sleep is a crucial factor for the psychological and physiological well-being of any human being. In Neonatal Intensive Care Units, preterm newborns’ sleep may be at risk due to medical and nursing care, environmental stimuli and manipulation. This review aims to identify the nurses’ interventions that promote sleep in preterm newborns in the Neonatal Intensive Care Units. An integrative review was conducted following Whittemore and Knafl’s methodology and the 2020 Preferred Reporting Items for Systematic Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…A total of 9,440 documents were searched in this study, and after de-duplication, reading the title, abstract and full text, 22 documents were finally included ( 10 , 12 , 22 , 24 , 25 , 31 - 47 ). These included two guidelines ( 34 , 36 ), 11 systematic reviews ( 10 , 22 , 25 , 31 - 33 , 35 , 38 , 41 , 42 , 45 ), 1 evidence summary ( 37 ), 1 technical report ( 24 ), 2 practice recommendations ( 12 , 39 ), and 5 randomized controlled trials ( 40 , 43 , 44 , 46 , 47 ). The basic characteristics of the included literature are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 9,440 documents were searched in this study, and after de-duplication, reading the title, abstract and full text, 22 documents were finally included ( 10 , 12 , 22 , 24 , 25 , 31 - 47 ). These included two guidelines ( 34 , 36 ), 11 systematic reviews ( 10 , 22 , 25 , 31 - 33 , 35 , 38 , 41 , 42 , 45 ), 1 evidence summary ( 37 ), 1 technical report ( 24 ), 2 practice recommendations ( 12 , 39 ), and 5 randomized controlled trials ( 40 , 43 , 44 , 46 , 47 ). The basic characteristics of the included literature are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to stress may result in sleep deprivation in preterm infants ( 8 ). For example, one study indicated that infants experience up to 234 interruptions in sleep within a 24-hour period ( 22 ). Despite increasing awareness among healthcare professionals about protecting sleep, the NICU is still considered a hostile environment.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that clinical education decreased overnight blood pressure checks, increased pediatric inpatient sleep duration, and reduced nighttime disruptions by clinicians. Similarly, in a study by Firmino et al, in 2022, it is shown that nurses can positively affect preterm newborns' sleep by controlling environmental stimuli and applying relaxation techniques and therapeutic positioning to their care practices [29]. However, Arregi et al, in 2022, found that no effect of environmental noise was found on sleep variables such as sleep habits and duration [30].…”
Section: │ Discussionmentioning
confidence: 99%
“…Worldwide, 2.4 million infants died in the neonatal period (first month of life) in 2020, accounting for 47% of all deaths of children less than five years old [ 1 ]. Neonates are at risk for many health-negative consequences after birth, such as hypothermia [ 2 ], hypoglycemia [ 3 ], infection [ 4 ], pain [ 5 ], sleep problems (especially in the Neonatal Intensive Care Units (NICUs)) [ 6 ], and stress (especially hospitalized neonates who are separated from mothers) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%